İstanbul'da sonradan minber konularak camiye çevrilen mescidler - Kaya, Maşide Betül (My University, 2019)
Müslümanların ibâdet mekânlarından minbersiz ve içinde hutbe okunmayan ve Cuma namazı kılınmayanlarına mescid, minberi olan hutbe okunup Cuma namazı kılınanlarına da cami denilmiştir. Mescidlerde ibâdet fonksiyonu daha ön plana çıkarken, camiler, içinde irad edilen hutbe ile İslam devlet geleneğinde devlet yönetimin meşruluğuna delalet etmektedir. Bu sebeple herhangi bir mescidde hutbe okutmak gücün ve bağlılığın simgesi olmuştur. Bu da yine İslam geleneğinde minberde temsil edilmiştir. Diğer İslam ülkelerinde olduğu gibi Osmanlı Devleti’nde de mescid ve cami geleneği devam etmiştir. İstanbul’da başlangıçta minbersiz olarak inşâ edilen mescidler, ilerleyen zamanlarda minber vaz’ edilerek camiye çevrilmişlerdir. Mescidden camiye dönüşümün tarihi planda bir takım sebepleri bulunmaktadır. İstanbul’da Sonradan Minber Konularak Camiye Çevrilen Mescidler konulu tez çalışmamızda bu sebepler, fıkhî, siyasî ve sosyal boyutuyla irdelenmiştir. Belirli bir döneme ait olmaksızın Osmanlı Dönemi’nde İstanbul’da camiye çevrilen mescidler, mescidlere minber vaz’ eden kişiler ve hangi tarihlerde minber vaz’ edildiği tespit edilmeye çalışılmıştır. Belgelerden de faydalanılarak mescidlerin camiye dönüşümü sonucunda vakıf görevlilerine yapılan tevcihatlar ve bu mescidlere konulan son döneme ait minberler üslûp bakımdan incelenmiştir.

Those praying houses which do not pulpit, Friday prayings are not fullfilled and sermons are not delivered after it are called masjids on the other hand, the ones which have pulpits, Friday prayings are fullfilled and sermons are delivered after then are called mosques. While functions of praying is always more important, in masjids, by the sermons delivered in the mosques, it is shown that administration of dynasty is legal in the Islamic state traditions. For this reason, to get delivered a sermon in a mosques became the sembol of power and devation. It was represented on a pulpit in Islamic tradition in this way. Just like in the other Islamic state, tradition of mosque and masjid tradition were carried on.The masjids which were built without pulpit before, were altered in a mosque by fixing pulpit later on in the meantime. Alteration of mosques from masjids have a number of reasons. In our study of thesis entitled The Masjids Which Were Converted into Mosques Later by Adding Pulpit in İstanbul later “those reasons were examined with in the dimensional canonical/ fıkhî, political and social views. Without focusing on a certain period, we tried to determine who did what dates, delivered sermons in the masjids which were altered into mosques in Istanbul during the whole Ottoman Era. By getting used of some documents, as a result of alteration of masjids into mosques, it was also examined from the view of appointments to the foundation authorities in charge and the pulpits which were fixed in those mosques were examined from the view of style.Those praying houses which do not pulpit, Friday prayings are not fullfilled and sermons are not delivered after it are called masjids on the other hand, the ones which have pulpits, Friday prayings are fullfilled and sermons are delivered after then are called mosques. While functions of praying is always more important, in masjids, by the sermons delivered in the mosques, it is shown that administration of dynasty is legal in the Islamic state traditions. For this reason, to get delivered a sermon in a mosques became the sembol of power and devation. It was represented on a pulpit in Islamic tradition in this way. Just like in the other Islamic state, tradition of mosque and masjid tradition were carried on.The masjids which were built without pulpit before, were altered in a mosque by fixing pulpit later on in the meantime. Alteration of mosques from masjids have a number of reasons. In our study of thesis entitled The Masjids Which Were Converted into Mosques Later by Adding Pulpit in İstanbul later “those reasons were examined with in the dimensional canonical/ fıkhî, political and social views. Without focusing on a certain period, we tried to determine who did what dates, delivered sermons in the masjids which were altered into mosques in Istanbul during the whole Ottoman Era. By getting used of some documents, as a result of alteration of masjids into mosques, it was also examined from the view of appointments to the foundation authorities in charge and the pulpits which were fixed in those mosques were examined from the view of style.Those praying houses which do not pulpit, Friday prayings are not fullfilled and sermons are not delivered after it are called masjids on the other hand, the ones which have pulpits, Friday prayings are fullfilled and sermons are delivered after then are called mosques. While functions of praying is always more important, in masjids, by the sermons delivered in the mosques, it is shown that administration of dynasty is legal in the Islamic state traditions. For this reason, to get delivered a sermon in a mosques became the sembol of power and devation. It was represented on a pulpit in Islamic tradition in this way. Just like in the other Islamic state, tradition of mosque and masjid tradition were carried on.The masjids which were built without pulpit before, were altered in a mosque by fixing pulpit later on in the meantime. Alteration of mosques from masjids have a number of reasons. In our study of thesis entitled The Masjids Which Were Converted into Mosques Later by Adding Pulpit in İstanbul later “those reasons were examined with in the dimensional canonical/ fıkhî, political and social views. Without focusing on a certain period, we tried to determine who did what dates, delivered sermons in the masjids which were altered into mosques in Istanbul during the whole Ottoman Era. By getting used of some documents, as a result of alteration of masjids into mosques, it was also examined from the view of appointments to the foundation authorities in charge and the pulpits which were fixed in those mosques were examined from the view of style.
Keywords: : İstanbul; Cami; Cuma; History; Islam; İslam; Juma; Masjid; Mescid; Minber Istanbul; Mosque; Pulpit